2018
DOI: 10.1002/ecs2.2464
|View full text |Cite
|
Sign up to set email alerts
|

Decadal effects of thinning on understory light environments and plant community structure in a subtropical forest

Abstract: 2018. Decadal effects of thinning on understory light environments and plant community structure in a subtropical forest. Ecosphere 9(10):Abstract. Canopy-opening disturbance such as thinning has immediate and substantive effects on understory microclimate and therefore the establishment and growth of understory plants. A large number of studies have reported the effects of thinning on tree growth, but few studies have examined long-term effects of thinning on understory light environments and species and func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 62 publications
1
17
0
1
Order By: Relevance
“…Most studies report that runoff increases after thinning (Andréassian, 2004; Brown et al, 2005; Buttle et al, 2019; Douglass, 1983; Grant et al, 2013; Hawthorne et al, 2013; Lane & Mackay, 2001; Sun et al, 2015), although the increases may last only a few years (Perry & Jones, 2017). However, forest thinning also reduces competition for resources (McLaughlin et al, 2013), and increased light, water, and nutrients may increase transpiration (Bladon et al, 2006; Boggs et al, 2015; Hernandez‐Santana et al, 2012) and release understory shrubs and trees (Ares et al, 2010; Tsai et al, 2018), potentially explaining the initial reduction in runoff. The reduction in runoff after thinning in N02 is consistent with reported reductions in streamflow after drought and insect outbreak‐induced tree mortality in arid and semi‐arid areas (Goeking & Tarboton, 2020; Guardiola‐Claramonte et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies report that runoff increases after thinning (Andréassian, 2004; Brown et al, 2005; Buttle et al, 2019; Douglass, 1983; Grant et al, 2013; Hawthorne et al, 2013; Lane & Mackay, 2001; Sun et al, 2015), although the increases may last only a few years (Perry & Jones, 2017). However, forest thinning also reduces competition for resources (McLaughlin et al, 2013), and increased light, water, and nutrients may increase transpiration (Bladon et al, 2006; Boggs et al, 2015; Hernandez‐Santana et al, 2012) and release understory shrubs and trees (Ares et al, 2010; Tsai et al, 2018), potentially explaining the initial reduction in runoff. The reduction in runoff after thinning in N02 is consistent with reported reductions in streamflow after drought and insect outbreak‐induced tree mortality in arid and semi‐arid areas (Goeking & Tarboton, 2020; Guardiola‐Claramonte et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several studies have reported that high diversity in the overstorey canopy has beneficial effects for understorey abundance and diversity [60], as a consequence of the light variability in the understorey layer that is created through the complementarity and overlapping of overstorey crowns [63][64][65]. As such, the abundance and diversity of understorey vegetation are positively affected by light heterogeneity [47,55,66], as predicted by the resource heterogeneity hypothesis.…”
Section: Lightmentioning
confidence: 94%
“…In contrast to stand-replacing wildfire that eradicates both overstorey and understorey vegetation, and releases soil nutrients through the combustion of coarse woody debris [15,69,118,120], clearcutting, which also removes overstorey vegetation, has a lesser impact on understorey vegetation [14,33,123]. Partial harvesting is divided into uniform harvesting and patch harvesting, both of which increase light availability and heterogeneity in the understorey, particularly with patch harvesting, and decrease the availability of soil moisture [66,119,[128][129][130].…”
Section: The Effects Of Forest Management Practices (Clearcutting Andmentioning
confidence: 99%
“…The light availability could decrease rapidly form short term to long term after thinning and return to the initial levels before thinning quickly [30,31]. In our study, the low thinning intensity (15% of the stock volume) led to a quick reclosure of the canopy three years after thinning.…”
Section: Temporal Effects Of Thinning On Light Availability and Soil mentioning
confidence: 50%
“…Much more attention has been paid to the effects of thinning intensity in previous studies [22,26,27]. However, the light availability (canopy openness) may obviously decrease over time after thinning due to the rapid growth of residual and regenerated trees or shrubs [28][29][30]. Most studies have reported the changes of light availability in the short term (1-3 years) after thinning [31], but the variations in the medium-and long-term after thinning remain unknown [32,33].…”
Section: Introductionmentioning
confidence: 99%